Quantity and quality of care and staff knowledge regarding people with Parkinson’s disease in long-term nursing care: “real-life” results from the German Care4PD study - Fründt, Odette; Lamb, Verena Caroline; Hanff, Anne-Marie; Mai, Tobias; Kirchner, Christiane; Amouzandeh, Ali; Buhmann, Carsten; Krüger, Rejko; Schnitzler, Alfons; Südmeyer, Martin (Frontiers in Aging Neuroscience, 2026)
IntroductionApproximately 20% of people with Parkinson’s disease (PwP) in Germany need professional long-term care (LTC). Previous data have indicated a rather poor LTC situation and the need for more profound analyses. Therefore, we aimed to assess the quantity and quality of LTC care for PwP and the knowledge on Parkinson’s disease (PD) in German LTC nursing staff.MethodsData from our nationwide, cross-sectoral Care4PD survey, which was distributed postally and online, were analyzed. Out of 295 completed anonymous LTC nurse questionnaires, 288 were included, with descriptive results presented in this study.ResultsIn terms of age and work experience, a representative sample of 288 participants, the majority (79%) of whom were registered LTC nurses, participated in the study. A total of 95% of them had certain experience with people with Parkinson’s disease (PwP). On average, each nurse supported approximately three PwP per week, with a mean care time of 48 min per day. A total of 17% of participants complained about “never” having enough staff, and 50% complained about “frequently changing” LTC personnel in their institution. Additionally, 10% reported “unsafe” care quality, with the occurrence of avoidable complications. Insufficient knowledge on PD and the importance of PD-specialized training were highlighted, with current training options often not recognized. Optimization suggestions consisted of more personnel and time capacities, educational measures, and interprofessional exchange.Discussion/conclusionImproving PwP care in German LTC facilities requires not only the general provision of more personnel and time resources but also, in particular, the development of greater expertise among LTC nursing staff to optimize care quality. The existing, but little-known, training opportunities should therefore be made known to a larger number of LTC nurses.